2004
DOI: 10.1111/j.1440-1819.2004.01224.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with intravenous hyperalimentation for severely anorectic patients and its outcome

Abstract: In treating patients with severe anorexia nervosa, it is important to improve their physical condition first. Patients who had lost close to 60% standard bodyweight (SBW) were candidates for inpatient treatment due to the mortality risk. With 80% SBW as the target for therapy, they were given both intravenous hyperalimentation and food by oral intake in order to improve their physical condition. In total, 51 patients were admitted. One died and four patients dropped out in the course of treatment. Forty-six pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 7 publications
1
12
1
Order By: Relevance
“…This study found good short-term nutritional outcomes of PN, but after a much longer hospital stay than in our experience. In our series the length of hospital stay was longer in PN-treated patients than in patients treated only by oral means, but was shorter than in two previous studies reporting patients with similar degrees of malnutrition [5,11]. Research that addresses the optimal length of hospitalization is scarce in this field.…”
Section: Discussioncontrasting
confidence: 74%
See 3 more Smart Citations
“…This study found good short-term nutritional outcomes of PN, but after a much longer hospital stay than in our experience. In our series the length of hospital stay was longer in PN-treated patients than in patients treated only by oral means, but was shorter than in two previous studies reporting patients with similar degrees of malnutrition [5,11]. Research that addresses the optimal length of hospitalization is scarce in this field.…”
Section: Discussioncontrasting
confidence: 74%
“…Also the comparison with these studies is not easy, because the first [11] referred to adult patients and the second [4] to adolescents who were less malnourished than those reported in our study. Tonoike et al [5], on the contrary, report their experience in 51 adult patients treated by PN, without a control group. This study found good short-term nutritional outcomes of PN, but after a much longer hospital stay than in our experience.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Criteria for life-saving intervention with artificial nutrition in anorexia nervosa patients Although it has always been stressed how crucial nutritional rehabilitation is in these patients, where only few studies are reporting the use of artificial nutrition in anorexia nervosa patients. Enteral nutrition and parenteral nutrition are both used in nutritional rehabilitation of severe anorexia nervosa patients (Paccagnella et al, 2006;Robb et al, 2002;Tonoike et al, 2004;Zuercher et al, 2003;Gentile et al, 2008;Gentile et al, 2010).…”
Section: Introductionmentioning
confidence: 99%